The hydric question in the context of cattle ranching production in the northern Mato Grosso Amazon: a framework of the main grievances (Research, Society and Development, 2022)
The objective of this study is to analyze the impacts of beef cattle on water resources in the North-Mato-Grossense Amazon. The study area (North 2) (IMEA, 2010) comprises 17 municipalities. The research opted for a qualitative approach, with bibliographic review procedures and a survey of regional socioeconomic data (PRODES and IBGE-SIDRA). As a reality approximation technique, between the years 2018 and 2021, 300 properties located along the BR-163 and state highways (MT-206, MT-208, MT-319, MT-320, MT-322) were visited for observation and photographic record. Sixty interlocutors with local experience were heard (technicians from the Environment and Agriculture Departments, municipal secretaries, ranchers, farmers, peasants, agronomists, biologists, among other professionals). It was recorded that, in addition of the forest suppression, there was a drastic reduction of riparian forests, compromising huge portions of water resources and resulting in serious problems. Furthermore, it was possible to see the watering of the animals directly in the water bodies, silting, inadequate soil management (crusting and poor recovery of pastures) and water resources (inadequate use of springs and streams, with channel alteration, inadequate and irregular sequential damming) that directly compromise the hydrological flow. Permanent Protection Areas (PPAs) – fixed in Brazilian legislation – were severely suppressed, reducing the springs, streams and rivers vitality, with consequent loss of ecological function. The pressure of productive activity is intense and the scenario could result in serious future water shortages.